Differential response of DU145 and PC3 prostate cancer cells to ionizing radiation: Role of reactive oxygen species, GSH and Nrf2 in radiosensitivity - Jayakumar, Sundarraj; Kunwar, Amit; Sandur, Santosh K.; Pandey, Badri N.; Chaubey, Ramesh C. (Biochimica et biophysica acta, 2014)
Radioresistance is the major impediment in radiotherapy of many cancers including prostate cancer, necessitating the need to understand the factors contributing to radioresistance in tumor cells. In the present study, the role of cellular redox and redox sensitive transcription factor, Nrf2 in the radiosensitivity of prostate cancer cell lines PC3 and DU145, has been investigated. Differential radiosensitivity of PC3 and DU145 cells was assessed using clonogenic assay, flow cytometry, and comet assay. Their redox status was measured using DCFDA and DHR probes. Expression of Nrf2 and its dependent genes was measured by EMSA and real time PCR. Knockdown studies were done using shRNA transfection. PC3 and DU145 cells differed significantly in their radiosensitivity as observed by clonogenic survival, apoptosis and neutral comet assays. Both basal and inducible levels of ROS were higher in PC3 cells than that of DU145 cells. DU145 cells showed higher level of basal GSH content and GSH/GSSG ratio than that of PC3 cells. Further, significant increase in both basal and induced levels of Nrf2 and its dependent genes was observed in DU145 cells. Knock-down experiments and pharmacological intervention studies revealed the involvement of Nrf2 in differential radio-resistance of these cells. Cellular redox status and Nrf2 levels play a causal role in radio-resistance of prostate cancer cells. The pivotal role Nrf2 has been shown in the radioresistance of tumor cells and this study will further help in exploiting this factor in radiosensitization of other tumor cell types. [Display omitted] •PC3 and DU145 cells showed differential radiation response.•Redox environment of DU145 cells is more reducing than that of PC3 cells.•Expression of Nrf2 and its dependent genes was higher in DU145 cells.•Biochemical inhibition and knockdown of Nrf2 led to radiosensitization.